Evaluation of Halal Certification Subsidy Policy on Awareness for MSMEs in West Java - Rahmawati, Pilda; Munandar, Aris (Social Impact Journal, 2025)
This study aims to evaluate the effectiveness of the halal certification subsidy policy on the awareness of MSMEs in West Java. Using a qualitative approach and a case study method in Sukabumi Regency, this research explores MSME actors' experiences and perceptions of the policy's implementation. The findings reveal that awareness tends to be administrative rather than ideological due to low halal literacy, limited assistance, and uneven information distribution. Analysis based on policy implementation theory shows that policy success is strongly influenced by implementation structure, problem complexity, and non-statutory factors such as local support. This study concludes that reformulating the implementation strategy through educational, participatory approaches and equitable resource distribution is essential to enhance MSMEs' substantial awareness and participation in halal policy sustainably.